FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DENGAN KEBIJAKAN DEVIDEN SEBAGAI VARIABEL PEMODERASI PADA PERUSAHAAN BASIC INDUSTRY DI BEI - Wardoyo, Teguh (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research aims to test and analyze whether capital structure, sales growth, company size have an effect on company value. Then the next objective is to test and analyze whether dividend policy is able to moderate capital structure, sales growth and company size on company value.This research is a type of explanatory research.The population of this research is public "basic materials" companies listed on the Indonesia Stock Exchange. The sampling method uses a purposive sampling method. The data analysis technique uses classic assumption tests, namely: multicollinearity test, autocorrelation test, heteroscedasticity test, and normality test. Hypothesis testing uses multiple regression analysis.The analysis used to process the data is moderated regression analysis with SPSS 23. The research results prove that sales growth has a positive and significant effect on company value as evidenced by The tcount value of 6.129 is greater than the ttable value of 1.684 and the significance value is 0.000 <0.050. Likewise, dividend policy is able to moderate company size on company value as evidenced by the tcount value of 2.838 being greater than the ttable value of 1.684 and a significance value of 0.008 < 0.050.